2008
DOI: 10.1038/bmt.2008.41
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between absolute lymphocyte count with PFS in patients with Hodgkin's lymphoma undergoing autologous hematopoietic cell transplant

Abstract: Previous reports in Hodgkin's lymphoma (HL) patients undergoing autologous hematopoietic cell transplantation (AHCT) have demonstrated a significant association between the absolute lymphocyte count at day 15 (ALC-15) with survival. To evaluate this finding further, we analyzed 146 patients with relapsed/refractory HL who underwent AHCT to evaluate the relationship between lymphocyte counts at apheresis and at two time points (days 15 and 90) after AHCT with PFS. We found no association between the ALC-15 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This was proven to be an independent prognostic factor in follicular lymphoma and DLBCL [4,13]. It has been validated as having prognostic value in Hodgkin's lymphoma [15] and acute myeloid leukemias as well [16]. It is very important to further categorize lymphocyte populations, as it is a dynamically changing population, consisting of several major cell types.…”
Section: Discussionmentioning
confidence: 97%
“…This was proven to be an independent prognostic factor in follicular lymphoma and DLBCL [4,13]. It has been validated as having prognostic value in Hodgkin's lymphoma [15] and acute myeloid leukemias as well [16]. It is very important to further categorize lymphocyte populations, as it is a dynamically changing population, consisting of several major cell types.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years a growing amount of research has shown that tumour microenvironment, host immunity, and inflammatory responses all play an important role in determining survival outcome of lymphoma. In this respect some have considered AMC as a surrogate biomarker of tumour‐associated macrophages within the tumour microenvironment 20 while others have regarded ALC as an important biomarker of tumour infiltrating lymphocytes (TILs) reflecting host immunity status, 21 and others have regarded ANC as a measure of the systemic inflammatory response to the tumor 22 . In this respect, inflammation is considered as a critical component of tumour progression, and it is evident that the tumour microenvironment, is largely coordinated by inflammatory cells, which play a central role in the neoplastic process by promoting proliferation, survival, and migration of tumour cells via activation of signaling pathways 23‐25 …”
Section: Discussionmentioning
confidence: 99%
“…In HL, low ALC,1 high AMC,2 and low lymphocyte to monocyte ratios2, 7 are associated with a poor prognosis. However until now, only a few studies have analyzed the prognostic significance of ANC and NLR in patients with HL.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have considered the absolute lymphocyte count (ALC)1 as an important biomarker of tumor infiltrating lymphocytes, reflecting host immunity status, while absolute monocyte count (AMC)2 serves as a surrogate biomarker of tumor‐associated macrophages within the tumor microenvironment, and the absolute neutrophil count (ANC)3 as a measure of the systemic inflammatory response to malignancy. Inflammation is regarded as a critical component of tumor progression, and it is evident that the tumor microenvironment, is largely coordinated by inflammatory cells, which play a central role in the neoplastic process, promoting, proliferation, survival, and migration of tumor cell via activation of signaling pathways 4, 5, 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation